Study on the possibility of applying the unified theory of acceptance and use of technology in online insurance business - HUYEN, DR. NGUYEN THANH; PHUONG, DR. NGUYEN THI THANH; TRANG, MA. TRAN THỊ THU; HUYEN, MA. LE THANH (The journal of contemporary issues in business and government, 2021)
In the context of the fourth technological revolution, online insurance has become a new trend of providing insurance products around the world. In Vietnam, some insurance companies have innovatively applied new technologies in their business activities, including online insurance. However, the field of online insurance is still in slow development and there have not been studies to find out about the degree of customer acceptance of this service. Therefore, the research team conducted a survey on customers 'demand for online insurance and researched the factors affecting customers' intention and behavior for using online insurance services through the Unified theory of acceptance and use of technology (UTAUT). The research team used structural equation modeling (SEM) to evaluate the relationship between the factors in the model. The research results show that risk perception, trust, social influence, and expected performance have an impact on customers' intention to use online insurance and the relationship between customers' intention and behavior for using online insurance.